Fan-noise reduction of data centre telecommunications' server racks, with an acoustic metamaterial broadband, low-frequency sound-absorbing liner - Bennett, Gareth (My University, 2023)
An acoustic metamaterial is evaluated successfully as a means to reduce axial fan noise in an IT server rack application. The continuing growth in demand for cloud-based memory storage is outpacing sustainable energy management which still requires the axial fan as a fundamental component in temperature control technologies. As chip temperatures increase, additional numbers of more powerful fans are required to run faster with the result that data centres have become unsafe working environments due to the acoustic output exceeding prescribed occupational noise level limits. Noise isolation using soundproof cabinets is expensive and impractical in data centres which seek to reduce floor space and communication losses. Instead, in this work, a 15 mm deep acoustic liner solution is proposed being the approach taken in the aeronautics sector to reduce aeroengine noise which, similarly, is a flow duct problem. The acoustic metamaterial adopted here is the recently developed Segmented Membrane Sound Absorber (SeMSA) which can be tailored for low frequency, broadband and tonal noise in a thin form-factor and which can be used in a grazing flow configuration. An equivalent circuit model developed for the SeMSA allows its design to be optimised to attenuate a typical server fan’s frequency spectrum. An array of manufactured rectangular SeMSA cells was embedded in a “deflector plate”, which is an existing component in a server rack. The deflector plate was implemented in a custom-built fan sound power rig, tested in an hemi-anechoic chamber and compared to a hardwall case and to PU foam. A relative overall decrease of 2.5 dBA was achieved for the SeMSA deflector plate liner which corresponds to a 43.9% decrease in overall sound emissions, which using a material thickness of only 15 mm, signifies an almost twofold increase in the time required for hearing damage to occur. A 3 dBA drop was achieved at the blade passing frequency of 620 Hz, while relative drops of 1–2.5 dBA were achieved from 2000–8000 Hz.
PUBLISHED
Keywords: Server rack; Data centre; Telecommunications noise; Occupational noise; Fan noise; Additive manufacturing techniques; Sound power reduction; Acoustic metamaterial; Decorated membrane; Micro-perforated panel absorber